2019
DOI: 10.3389/fpsyg.2019.00020
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Stress Before a Nap Increases Sleep Latency and Decreases Early Slow-Wave Activity

Abstract: Sleep disturbances are an important risk factor for stress-related diseases such as burnout or depression. In particular, slow-wave activity (SWA) during sleep might be eminently relevant for optimal maintenance of mental health and cognitive functioning. In spite of the clinical importance and the pertinence of stress-related processes in everyday life, the physiological mechanisms of the association between stress, sleep, and cognition are not well-understood. In the present study, we carefully mapped the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
23
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 58 publications
7
23
4
Order By: Relevance
“…Notably, we did not find any differences in SWS oscillatory events between the stress and control groups. This differs from previous research, which has found that psychosocial stress impacts the architecture of subsequent sleep, in particular reducing SWS time and reducing slow wave (0.5Hz-4.5Hz) oscillatory power (Ackermann et al, 2019;Kim & Dimsdale, 2007). There are several possible reasons for this discrepancy.…”
Section: Discussioncontrasting
confidence: 92%
“…Notably, we did not find any differences in SWS oscillatory events between the stress and control groups. This differs from previous research, which has found that psychosocial stress impacts the architecture of subsequent sleep, in particular reducing SWS time and reducing slow wave (0.5Hz-4.5Hz) oscillatory power (Ackermann et al, 2019;Kim & Dimsdale, 2007). There are several possible reasons for this discrepancy.…”
Section: Discussioncontrasting
confidence: 92%
“…Critically, sleep disturbances are highly prevalent after trauma (70-91%; Maher, Rego, & Asnis, 2006) and have been identified as a risk factor for persistent PTSD (Babson & Feldner, 2010;Marcks, Weisberg, Edelen, & Keller, 2010). Experimental evidence (Ackermann, Cordi, La Marca, Seifritz, & Rasch, 2019;Sopp, Brueckner, Schäfer, Lass-Hennemann, & Michael, 2019) further indicates that sleep disturbances can arise as a direct result of ('traumatic') stress. Thus, sleep could act as an early modulator of intrusive re-experiencing.…”
Section: Discussionmentioning
confidence: 99%
“…Although a relatively large literature examines relations between the experience of chronic daytime stress and sleep disruption ( Hall et al, 2007 ; Mezick et al, 2009 ; Hall et al, 2017 ), few studies have examined whether cognitive processes are affected by the experience of laboratory-induced stress immediately before bedtime (and none have examined whether next-day retrieval/execution of a PM intention encoded prior to sleep is affected by such an experience). This question is of interest because self-reported bedtime stress affects sleep quality negatively ( Åkerstedt et al, 2012 ), and laboratory-induced acute psychosocial stress experienced immediately prior to a nap increases sleep latency and decreases slow-wave activity ( Ackermann et al, 2019 ). The mechanisms underlying these effects appear to be related to the increases in sympathetic arousal and cortisol (CORT) concentrations provoked by the experience of stress ( McEwen et al, 2015 ; Sapolsky, 2015 ).…”
Section: Introductionmentioning
confidence: 99%